Comparative literature, literary theory and the anxiety of omission - Domínguez, César (Primerjalna književnost, 2007)
Analysis of comparative literature's institutionalization together with literary theory in Spain. Special attention is paid to the benefits and constraints of this alliance, which is tantamount to a discussion of the new paradigm championed in the 80s. The paucity of comparative literature's presence in theoretical research is identified as a sign of literary theory's Euro-Americancentrism.
Keywords: primerjalna književnost; comparative literature; primerjalna literarna veda; literarna teorija; literary theory; Spain; Španija; univerzitetni programi